Forecasting the next shot location in tennis using fine-grained spatiotemporal tracking data - Wei, X.; Lucey, P.; Morgan, S.; Sridharan, S. (IEEE Transactions on Knowledge and Data Engineering, 2016)
In professional sport, an enormous amount of fine-grain performance data can be generated at near millisecond intervals in the form of vision-based tracking data. One of the first sports to embrace this technology has been tennis, where Hawk-Eye technology has been used to both aid umpiring decisions, and to visualize shot trajectories for broadcast purposes. Despite the high-level of accuracy of the tracking systems and the sheer volume of spatiotemporal data they generate, the use of this data for player performance analysis and prediction has been lacking. In this research, we use ball and player tracking data from "Hawk-Eye" to discover unique player styles and predict within-point events. We move beyond current analysis that only incorporates coarse match statistics (i.e., serves, winners, number of shots, and volleys) and use spatial and temporal information which better characterizes the tactics and tendencies of each player. Using a probabilistic graphical model, we are able to model player behaviors which enables us to: 1) find the factors such as location and speed of the incoming shot which are most conducive to a player hitting a winner (i.e., "sweet-spot") or cause an error, and 2) do "live in-point" prediction - based on the shots being played during a rally we estimate the probability of the outcome (e.g., winner, continuation, or error) and the location of the next shot. As player behavior depends on the opponent, we use model adaptation to enhance our prediction. We show the utility of our approach by analyzing the play of Djokovic, Nadal, and Federer at the 2012 Australian Tennis Open.